Globalización y posmodernidad: desafíos al aprendizaje - Barberousse, Paulette (2002)
At a time when academic discourse is less listened to and the messages of publicists, journalists and writers of the so called “light texts” cause a much greater impact on the people, a question arises: Which ethical stand can a college professor take in postmodern times? In the global village, the most powerful economic forces take a toll on people and cultures everywhere alike. In the rapid expansion of globalization, the transmission of information plays a critical role. "To be an academic" in postmodern times implies a major challenge, for knowledge cannot be transformed easily into consumers' goods, without running the risk of losing its essence when transformed into another market commodity. It looks as if in the mid of a desolating panorama, only the strengthening of the person in his/her own experiences, thoughts, wishes and feelings can lead us towards a utopia, namely, to dream and recreate a university aimed humanity's well-being.